PENGARUH PENDAPATAN ASLI DAERAH, DANA PERIMBANGAN, BELANJA MODAL, PERTUMBUHAN EKONOMI TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH KABUPATEN/KOTA DI PROVINSI BENGKULU - Dhicky, Agung Setyo; Perdanakusuma, Fathul Hilal (Jurnal Ilmu Akuntansi, 2023)
The purpose of this study was to determine whether economic growth affects the financial performance of district / city governments in Bengkulu province. the data source used in this study is secondary data. The sample used in this study was saturated method. which amounted to 10 (ten) consisting of 9 (nine) regencies and 1 (one) municipality in Bengkulu Province. The total sample studied for 1 year period 2019 - 2021, so there were 30 samples. The results showed that PAD had a significant effect on Local Government Financial Performance. Fiscal Balance Fund has no significant effect on Government Financial Performance Capital Expenditure has no significant effect on Local Government Financial Performance. Economic Growth has no significant effect on Local Government Financial Performance.